Performance of police personal protective equipment challenged with a military grenade. (September 2019) - Williams, MGG; Turner, GR; Lee, M; Smith, BD; Carr, DJ; Malbon, C; Nelson, E
Police body armour in the United Kingdom (UK) is designed to provide protection from edged weapons and low-velocity pistol ammunition. Recent events have raised concern about whether UK police body armour and associated personal protective equipment (PPE) provides protection from military threats such as improvised explosive devices (IED) and grenades. In this paper PPE worn by specialised police officers was assessed for its protective performance from a specified grenade threat. The major cause of injury suffered by police officers challenged by a modern military grenade would be from the associated fragmentation which perforated coveralls, boots, helmet and soft body armour, but not hard armour plates.